STUDY OF THE UTILIZATION OF COAL ASH AS COVER LAYERING MATERIAL TO PREVENT THE FORMATION OF ACID MINE DRAINAGE AT PT ADARO INDONESIA - TIARASANI SONDAKH (NIM : 12113094), GHEA
Mining activity is characterized by the activity of the excavation and stockpiling. Soil and rocks are then dumped on a disposal area or backfilled. Excavation and dumping activities will lead to exposure of sulphide minerals from rock to allow contact with air or rainwater. Mine Acid Drainage (AMD) is characterized by low pH levels. The formation of the AMD that has happened will be difficult to discontinue, as it is a continuous process until one of its reactants runs out. Acid Mine Drainage (AMD) formation can be prevented by using encapsulation method. This method is done by preventing the reaction between the sulfide material with air and/or water, practically is by covering Potentially Acid Forming (PAF) material with a certain thickness of Non-Acid Forming (NAF) material. Due to the least amount of NAF material in the field, the fly ash material is used as cover layering material. Some tests were conducted to determine the characteristics of overburden and fly ash: static test, element tests (Induced Coupled Plasma - Mass spectrometry and X-Ray Fluorescence), mineralogical test (X-Ray Diffraction), physical tests, and kinetic test (Free Drainage Column Leach Test). Based on those tests, it was found that the geochemical characteristics of the overburden is PAF and fly ash is NAF. The grain size of the overburden material (sample code: PAF-HC) is sandysilt, while the grain size of fly ash is silt. PAF-HC has high plasticity properties, while fly ash has moderate plasticity properties. The fly ash sample plasticity limit higher than the PAF-HC sample may cause the fly ash material to crack first than the PAF-HC sample. So it can cause coating performance to decrease dramatically. Oxidation reactions and oxygen diffusion are still possible in this layer. PAF-HC and fly ash are not chemically reactive in the layering method; while based on mixing method, those samples are chemically reactive (the thickness of the fly ash will affect the ion release neutralizer / alkalinity). Based on those tests, it can be concluded that fly ash from PT Adaro Indonesia can not be used as a preventative material for AAT formation by using layering method.